Realizing Political Leadership with Integrity Through Political Education: A Study of KOMPAK-API - Maskur, Muhammad Azil; Fikri, Wildan Azkal; Indraswara, Dede (Indonesian Journal of Legal Community Engagement, 2024)
Political leadership with integrity is a must in realizing a golden Indonesia. However, corruption then becomes something that hinders leadership with integrity. Because of this, this study was conducted by the Anti-Corruption Counselor Community Forum-Integrity Building Experts (KOMPAK-API) which focuses on the realization of leadership with integrity through political education. This study raises the formulation of the problem in the form of What is the role of KOMPAK-API in conducting political education in Central Java? How can political education lead to the birth of political leadership with integrity? The study was conducted using a qualitative-descriptive method and found answers regarding the close relationship between political education carried out by KOMPAK-API and political leadership with integrity in Central Java. Political education is carried out at elementary school, high school, and university levels. Not only for students but also for all teachers. Based on this, political education is recognized as being able to realize political leadership with integrity in order to achieve a Golden Indonesia in 2045.